2013
DOI: 10.5455/gmj-30-2013-123
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, laboratory, and echocardiographic features of patients with pericardial effusion in Gaziantep region

Abstract: ÖzetMalakoplaki, kronik granülomatöz inflamatuar bir reaksiyondur. Sıklıkla immün baskılanmış hastalarda oluşur. Makrofajların uygun bir şekilde fagositoz yapamadığı bakteriyel infeksiyona karşı sıra dışı cevabı temsil ettiğine inanılır. En sık üriner ve gastrointestinal sistemi tutar. Spesifik klinik semptomu yoktur. Tanısı histopatolojik inceleme ile konulur. Klinikte üretral kitle ön tanısı ile gönderilen ve histopatolojik inceleme ile malakoplaki tanısı alan olgumuzu literatür eşliğinde sunmayı amaçladık. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(2 reference statements)
0
1
0
Order By: Relevance
“…included 104 patients in a study where they found that idiopathic causes were the most common on es (16). Another study conducted in Turkey including 123 patients with pericardial effusion found that 31.1% of the etiology was associated with idiopathic causes (17). In another study conducted by Strobbe et al and including 269 patients undergoing pericardiocentesis in the past 10 years, they found that the etiology was idiopathic in 26% of the cases, and associated with malignancy in 25% (18).…”
Section: Discussionmentioning
confidence: 99%
“…included 104 patients in a study where they found that idiopathic causes were the most common on es (16). Another study conducted in Turkey including 123 patients with pericardial effusion found that 31.1% of the etiology was associated with idiopathic causes (17). In another study conducted by Strobbe et al and including 269 patients undergoing pericardiocentesis in the past 10 years, they found that the etiology was idiopathic in 26% of the cases, and associated with malignancy in 25% (18).…”
Section: Discussionmentioning
confidence: 99%